An integrated teaching model to develop english proficiency of ESL management students - Varghese, Rosemary (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
The gap between receptive and productive English language skills is perceived to be unusually large among ESL students in the culturally segregated states of India. While the students’ listening and reading comprehension skills strengthen with class lectures and reading assignments, their speaking and writing skills remain underdeveloped. The purpose of this study is to create an integrated teaching model to improve the English proficiency of management students in order to make them more employable. The model combines two models of curriculum design with two models of teaching methodology. Using the basic ESP model of curriculum design, the other models are incorporated into it to achieve three objectives, to reduce the unusually wide gap between receptive and productive language skills, to gain proficiency in business communication tasks and to improve identified language deficiencies. The model is applied to a sample of ESL management students. The business communication tasks required at the corporate level as well as the language deficiencies of the respondents are assessed and are used to create the course design. Their motivation and attitude levels are measured. Learner-centered assessment techniques and learning styles are analysed in order to incorporate these into the teaching learning process. Along with the teaching methodology suggested in the model, these inputs provide the entire framework for an intervention that aims to achieve the stated objectives.